Clinical Trials for Gene Therapy in Lysosomal Diseases With CNS Involvement - Sevin, Caroline; Deiva, Kumaran (Frontiers in Molecular Biosciences, 2021)
There are over 70 known lysosomal storage disorders (LSDs), most caused by mutations in genes encoding lysosomal hydrolases. Central nervous system involvement is a hallmark of the majority of LSDs and, if present, generally determines the prognosis of the disease. Nonetheless, brain disease is currently poorly targeted by available therapies, including systemic enzyme replacement therapy, mostly (but not only) due to the presence of the blood–brain barrier that restricts the access of orally or parenterally administered large molecules into the brain. Thus, one of the greatest and most exciting challenges over coming years will be to succeed in developing effective therapies for the treatment of central nervous system manifestations in LSDs. Over recent years, gene therapy (GT) has emerged as a promising therapeutic strategy for a variety of inherited neurodegenerative diseases. In LSDs, the ability of genetically corrected cells to cross-correct adjacent lysosomal enzyme-deficient cells in the brain after gene transfer might enhance the diffusion of the recombinant enzyme, making this group of diseases a strong candidate for such an approach. Both in vivo (using the administration of recombinant adeno-associated viral vectors) and ex vivo (auto-transplantation of lentiviral vector-modified hematopoietic stem cells-HSCs) strategies are feasible. Promising results have been obtained in an ever-increasing number of preclinical studies in rodents and large animal models of LSDs, and these give great hope of GT successfully correcting neurological defects, once translated to clinical practice. We are now at the stage of treating patients, and various clinical trials are underway, to assess the safety and efficacy of in vivo and ex vivo GT in several neuropathic LSDs. In this review, we summarize different approaches being developed and review the current clinical trials related to neuropathic LSDs, their results (if any), and their limitations. We will also discuss the pitfalls and the remaining challenges.